Assistive technology self-management intervention for older Hispanics: a feasibility study. (16th November 2020) - Orellano-Colón, Elsa M.; Harrison-Cruz, Stephanie; López-Lugo, Edith; Ramos-Peraza, Stephanie; Meléndez-Ortiz, Alexandra; Ortiz-Torres, Johan; Rodríguez-Marrero, Janice
Abstract: Purpose: Even though assistive technology (AT) can overcome disabilities, Hispanics are among the least likely to use AT. We aimed to assess the feasibility of an assistive technology AT and disability self-management intervention concerning recruitment, retention, adherence, acceptability, preliminary evaluation of participants' responses to intervention and preliminary efficacy. Methods: We used mixed-method intervention design with a pre- and post-test quantitative model with an experimental intervention and qualitative data obtained after the intervention. Ten older Hispanics were enrolled in an eight weeks group intervention. Instruments to measure feasibility and pre/post participants' report outcomes of quality of life (Psychosocial Impact of Assistive Device Scale [PIADS] Short Form), global health (PROMIS General Health Short Form), self-efficacy (Self-efficacy Scale) and performance difficulties (Individualized Prioritized Problem Assessment [IPPA]) were used. Results: Recruitment, retention and adherence rates were high, the intervention was acceptable, and the participants reported outcomes, such as: new knowledge and skills, enhanced activity performance and participation, increased safety and willingness to use AT, decreased performance difficulties and enhanced quality of life. Conclusion: The intervention was feasible and acceptable and is promising in decreasing performance difficulties in daily activities as well as in having a positive impact in older Hispanics' quality of life. IMPLICATIONS FOR REHABILITATION: Older Hispanics living in Puerto Rico experience a high prevalence of disabilities in independent living. In a relative small sample this study shows that an assistive technology (AT) and disability self-management intervention for older Hispanics living in Puerto Rico is feasible to be delivered in a group format and in the community context. Older Hispanics living in Puerto Rico can potentially decrease performance difficulties in daily living activities and improved their quality of life through assistive technology and disability self-management interventions.